The APPLICATION OF VIDEO CONFERENCING IN HUNGARIAN PRISONS - Juhász, Zsuzsanna (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Abstract: The application of the different solutions of video communication are getting more and more popular in the field of criminal justice. Video conferencing technology can be used for legal proceedings that would otherwise require transporting the prisoner and utilizing other staff resources. The purpose of the present study is to briefly introduce video conferencing and its effect on the prison environment.
Keywords: video conferencing, courtroom, prison setting, prisoners